2021
DOI: 10.1177/23993693211001374
|View full text |Cite
|
Sign up to set email alerts
|

Onco-hypertension: Overview of hypertension with anti-cancer agents

Abstract: Onco-hypertension is an emerging field investigating the relationship between hypertension and cancer. This paper details one part of this relationship—the effect of anti-cancer agents on blood pressure. We review the evidence linking targeted therapies, immunotherapy, traditional chemotherapies, and hormonal agents with hypertension. Proposed pathophysiological mechanisms vary by drug but include endothelial dysfunction, altered sodium homeostasis, and nephrotoxicity. Despite growing interest in the field, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 112 publications
(158 reference statements)
0
9
0
2
Order By: Relevance
“…However, it has been suggested that a decrease in downstream hsp70 (heat shock protein 70) may be associated along with decreased PI3K (phosphatidylinositol 3-kinase) signaling resulting in downstream depletion of NO production and reduced VEGF propagation with eventual vascular remodeling and endothelial cell dysfunction. 13,121,128,129…”
Section: Clinical and Epidemiological Evidence For Btki-induced Hyper...mentioning
confidence: 99%
See 4 more Smart Citations
“…However, it has been suggested that a decrease in downstream hsp70 (heat shock protein 70) may be associated along with decreased PI3K (phosphatidylinositol 3-kinase) signaling resulting in downstream depletion of NO production and reduced VEGF propagation with eventual vascular remodeling and endothelial cell dysfunction. 13,121,128,129…”
Section: Clinical and Epidemiological Evidence For Btki-induced Hyper...mentioning
confidence: 99%
“…227 Navigating the complexity of decisions around antihypertensive treatment selection with consideration of drug pharmacokinetics and pharmacodynamics, with the appreciation of both potential side effects and individual patient comorbidities requires a multidisciplinary approach and supports a shift in our practice of CVD management in patients with cancer towards an individualized approach within the growing concept of oncohypertension. 11,13,211,222…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
See 3 more Smart Citations